Assessment of microbial viability in municipal sludge following ultrasound and microwave pretreatments and resulting impacts on the efficiency of anaerobic sludge digestion - AKGÜL, DENİZ (SPRINGER, 2016)
A range of ultrasonication (US) and microwave irradiation (MW) sludge pretreatments were compared to determine the extent of cellular destruction in micro-organisms within secondary sludge and how this cellular destruction translated to anaerobic digestion (AD). Cellular lysis/inactivation was measured using two microbial viability assays, (1) Syto 16A (R) Green and SytoxA (R) Orange counter-assay to discern the integrity of cellular membranes and (2) a fluorescein diacetate assay to understand relative enzymatic activity. A range of MW intensities (2.17-6.48 kJ/g total solids or TS, coinciding temperatures of 60-160 A degrees C) were selected for comparison via viability assays; a range of corresponding US intensities (2.37-27.71 kJ/g TS, coinciding sonication times of 10-60 min at different amplitudes) were also compared to this MW range. The MW pretreatment of thickened waste activated sludge (tWAS) caused fourfold to fivefold greater cell death than non-pretreated and US-pretreated tWAS. The greatest microbial destruction occurred at MW intensities greater than 2.62 kJ/g TS of sludge, after which increased energy input via MW did not appear to cause greater microbial death. In addition, the optimal MW pretreatment (80 A degrees C, 2.62 kJ/g TS) and corresponding US pretreatment (10 min, 60 % amplitude, 2.37 kJ/g TS) were administered to the tWAS of a mixed sludge and fed to anaerobic digesters over sludge retention times (SRTs) of 20, 14, and 7 days to compare effects of feed pretreatment on AD efficiency. The digester utilizing MW-pretreated tWAS (80 A degrees C, 2.62 kJ/g TS) had the greatest fecal coliform removal (73.4 and 69.8 % reduction, respectively), greatest solids removal (44.2 % TS reduction), and highest overall methane production (248.2 L CH4/kg volatile solids) at 14- and 7-day SRTs. However, despite the fourfold to fivefold increases in cell death upon pretreatment, improvements from the digester fed MW-pretreated sludge were marginal (i.e., increases in efficiency of less than 3-10 %) and likely due to a smaller proportion of cells (10-20 %) in the polymeric network and mixed sludge fed to digesters.
Keywords: Anaerobic digestion; Sludge pretreatment; Microwave irradiation; Ultrasonication; Microbial viability; Municipal waste; WASTE-ACTIVATED-SLUDGE; PHYSIOLOGICAL-STATE; BACTERIAL-CELLS; WATER; DISINTEGRATION; COMMUNITIES; RADIATION